(untitled) (Лучшие интеллектуальные исследования, 2024)
This article examines the role of automated programming tools in improving productivity in the development process. Code generators, test automation tools, and CI/CD processes help developers reduce errors, save time, and create better software. The article highlights the advantages of automation and its importance in the field of programming.